Real-world experience of first-line afatinib in patients with EGFR-mutant advanced NSCLC: a multicenter observational study - Chai, Chee Shee; Ho, Gwo Fuang; Adlinda, Alip; Mohd Ibrahim, Abd Wahid; Matin Mellor, Abdullah; Foo, Yoke Ching; How, Soon Hin; Adel, Zaatar; Lam, Kai Seng; Leong, Kin-Wah; Low, JohnbSeng Hooi; Mastura, Md Yusof; et al. (Springer Nature, 2019)
Background: This study aimed to evaluate the efficacy, side-effects and resistance mechanisms of first-line afatinib in a real-world setting.